Outer Hair Cell and Auditory Nerve Function in Speech Recognition in Quiet and in Background Noise - Hoben, Richard; Easow, Gifty; Pevzner, Sofia; Parker, Mark A. (Frontiers in Neuroscience, 2017)
The goal of this study was to describe the contribution of outer hair cells (OHCs) and the auditory nerve (AN) to speech understanding in quiet and in the presence of background noise. Fifty-three human subjects with hearing ranging from normal to moderate sensorineural hearing loss were assayed for both speech in quiet (Word Recognition) and speech in noise (QuickSIN test). Their scores were correlated with OHC function as assessed via distortion product otoacoustic emissions, and AN function as measured by wave 1 amplitude, latency, and threshold of the evoked auditory brainstem response (ABR). Speech and ABR stimuli were presented at equivalent sensation levels in order to control for the degree of hearing sensitivity across patients. The results indicated that 1) OHC dysfunction was evident in the lower range of normal audiometric thresholds, which demonstrates that hidden hearing loss can occur form OHC damage, 2) AN dysfunction was evident beginning at mild levels of hearing loss, 3) there were no correlations between neither speech in quiet nor speech in noise performance and wave I amplitude when OHC function was normal and AN activity was dysfunctional, 4) speech in noise performance decreased when both OHC and AN responses were dysfunctional, 5) subjects with OHC dysfunction exhibited increased speech in quiet performance at or near threshold when stimuli were presented at equivalent sensation levels. The results are best described using linear systems theory where OHCs function as a bank of frequency and intensity filters that fine tune the speech signal. These results show that OHC dysfunction contributes to hidden hearing loss, the combined functions of both OHCs and the AN are required for optimum speech in noise performance, and that persons with sensorineural hearing loss exhibit better word discrimination in quiet at or near their audiometric thresholds than normal listeners.